Chinese Elderly Studies : An Analysis on the Daily Activities and Their Associations of the Chinese Elderly - Wagner, Michelle; Benner, Ann; Ji, Jianjun (My University, 2018)
Using data from a national survey conducted by the China Research Center on Aging (CRCA) in 2006, this study seeks to examine the relationship between the ability of the Chinese elderly to perform the Activities of Daily Living (ADL) which includes cooking, eating, walking, toileting, getting in and out of bed, bathing, and dressing independently. Factors such as demographic location, gender, socioeconomic status, and other psychological factors are taken into account.
Color poster with text, tables, and graphs.
Keywords: Elderly people; Senior care; Posters